Pengaruh Capital Expenditure dan Struktur Modal terhadap Nilai Perusahaan pada Index Saham LQ45 Yang Terdaftar Di Bursa Efek Indonesia - Kusnia, Fiatul; Suyanto, Suyanto; Padwa Sari, Gustin (Expensive: Jurnal Akuntansi dan Keuangan, 2024)
The growth opportunities of each company are different from each other. These differences lead to different financial decisions to achieve company goals. This study discusses the impact of capital expenditure (CAPEX) and capital structure (DER) on company value (PBV) in LQ-45 stock index companies listed on the Indonesia Stock Exchange. The purpose of this study is to understand the influence of CAPEX and DER on LQ-45 stock index companies listed on the Indonesia Stock Exchange in 2021-2022. The sample used was 56 LQ-45 stock index companies.Data collection techniques use documentation techniques, literature, and access to the official website of the Indonesia Stock Exchange and the website of each company in accordance with the research sample in the form of annual report data. While the data analysis techniques used are descriptive tests, classical assumption tests, multiple linear regression analysis, partial T tests, F tests, and determination tests (R2). The results showed that capital expenditure does not affect the value of the company, the capital structure affects the value of the company.